Drip infusion cholangiography with CT in cats. Issue 12 (December 2018) - Tanaka, Toshiyuki; Akiyoshi, Hideo; Mie, Keiichiro; Shimazaki, Hitoshi; Ohashi, Fumihito
Objectives: Ultrasonography can detect extrahepatic biliary obstructions. However, visualisation of part of the bile duct using ultrasonography can be technically difficult if there is overlying bowel gas. This study investigated the safety and value of drip infusion cholangiography with computed tomography (DIC-CT) in the visualisation of the bile duct in healthy cats and extrahepatic biliary obstruction in cats with cholelithiasis. Methods: DIC-CT was performed in three healthy cats and two cats with cholelithiasis. Meglumine iotroxate was administered by intravenous drip infusion over 30 mins. The attenuation value was measured perpendicular to the lumen by a region of interest covering about 50% of the area of the lumen. Results: The bile ducts were visualised successfully with DIC-CT in all healthy cats without any significant adverse events. The attenuation value of the contrast medium was 271 ± 37 HU. In the two cats with cholelithiasis, the presence or absence of extrahepatic biliary obstruction was determined using DIC-CT without any significant adverse events. The attenuation value of cholelithiasis in the cat with an extrahepatic biliary obstruction was 933 ± 119 HU. In the cat with no extrahepatic biliary obstruction, the attenuation value of the contrast medium was 249 ± 53 HU and the attenuation value of cholelithiasis was 167 ± 28 HU. Conclusions and relevance: DIC-CT visualises bile ducts and detects obstructive biliary disease without significant adverse events. Therefore, it appears to be a safe procedure for visualisation of the bile duct in cats.